Numerical Study on the Longitudinal Response Characteristics of Utility Tunnel under Strong Earthquake: A Case Study - Guoyi Tang; Yumei Fang; Yi Zhong; Jie Yuan; Bin Ruan; Yi Fang; Qi Wu (Advances in Civil Engineering)
In this paper, the longitudinal seismic response characteristics of utility tunnel subjected to strong earthquake was investigated based on a practical utility tunnel project and numerical method. Firstly, the generalized response displacement method (GRDM) that was used to conduct this study was reviewed briefly. Secondly, the information of the referenced engineering and the finite element model was introduced in detail, where a novel method to model the joints between utility tunnel segments was presented. Thirdly, a series of seismic response of the utility tunnel were provided, including inner force and intersegment opening width. The results showed that (i) the seismic response of the utility tunnel under far-field earthquake may be remarkable and even higher than that under near-field earthquake; (ii) sharp variation of response may occur at the interface between “soft” soil and “hard” soil, and the variation under far-field earthquake could be much more significant. This research provides a reference for the scientific study and design of relevant engineering.